2018
DOI: 10.1111/imj.13652
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with the spiralling price of medicines: issues and solutions

Abstract: Escalating cost of medicines is rapidly becoming a serious threat to patients and health systems. This trend has been documented to impact patient outcomes adversely. As clinicians and tax payers, it is our responsibility to be aware of the potential detrimental effects spiralling costs have on our patients, our community and our health system and to mitigate these effects by exposing this issue to our respective professional societies, representatives of the pharmaceutical companies that we interact with, gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…We believe the updated review will help people better understand the benefits and harms of the different treatments in heterogeneous populations in the ‘real world,’ reflecting conditions in routine clinical practice [50, 51]. This is important given the increasing costs of treatments for cancer, increasing pressure on available resources [26, 27, 34, 5254], and the extent of current litigation surrounding these three MoAbs in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…We believe the updated review will help people better understand the benefits and harms of the different treatments in heterogeneous populations in the ‘real world,’ reflecting conditions in routine clinical practice [50, 51]. This is important given the increasing costs of treatments for cancer, increasing pressure on available resources [26, 27, 34, 5254], and the extent of current litigation surrounding these three MoAbs in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we analyze the practical implications of the neoliberal free market perspective of Hayek, CST, and RPH in a case study about serving the public interest in the pharmaceutical sector. Recently, the pharmaceutical industry has been negatively covered in the press and in academic publications, for example, regarding the outrageously expensive cost of so-called orphan drugs (drugs for rare diseases that affect small numbers of individuals) (Davies, Fulton, Brook, & Hughes, 2017; Ma, Danta, Day, & Ma, 2018; Prasad, De Jesus, & Mailankody, 2017). This development was encouraged by orphan drug legislation in the United States and Europe that aimed to make the development of such drugs profitable.…”
Section: Application To the Pharmaceutical Industrymentioning
confidence: 99%
“…They found that between 1988 and 2009, pharmaceutical companies enjoyed substantially higher profit margins than other companies, while investing proportionately less in R&D than other high-R&D firms. Therefore it is suggested that high prices of medicines are primarily related, not to high R&D costs, but to the lack of market competition (Ma et al, 2018).…”
Section: Application To the Pharmaceutical Industrymentioning
confidence: 99%
“…This last observation is, in fact, part of a wider debate on the actual form of innovation in cancer drugs and the setting up of most clinical trials. Currently, an explosive and unacceptable increase in costs accompanies the development and marketing of anti-cancer drugs [67][68][69]. Combined with unrepresentative results in very limited patient cohorts, insignificant clinical benefits, and more than occasionally, concomitant impairment of patients' quality of life, the actual clinical research paradigm seems to have outlasted its value in its current form [68,[70][71][72].…”
Section: So What?mentioning
confidence: 99%